Localized Sinonasal Amyloidosis - Nur Wahidah Wahid MBBS, MSc, MRCS(ENT); Tarik Abed MBBS, EBEORL-HNS; Sheneen Meghji MBChB, BSc, MRCS(ENT); Janet Gilbertson CSci, FIBMS; Martyn Barnes MBBS, BSc, MSc, MD, FRCS (Allergy & Rhinology, 2019)
Localized amyloidosis involving the nasal mucosa is rare, with only 38 published cases reported to date. We report a case of amyloidosis localized to the sinonasal tract. A 61-year-old man presented with a 1-year history of left-sided nasal obstruction. Endoscopic examination and computed tomography revealed the presence of a nasal mass originating from the left inferior turbinate. The patient subsequently underwent an examination under anesthesia and an excision biopsy of the nasal mass. Histology confirmed amyloidosis with no immunospecific stains. Systemic amyloidosis testing was negative, leading to a diagnosis of localized sinonasal amyloidosis of nonamyloid A (AA) subtype. To our knowledge, this is the second reported case of non-AA subtype of the sinonasal tract. The patient was managed conservatively and is currently under close follow-up.